Application of the name Lemna punctata G. Mey., the type of Landoltia Les & D. J. Crawford1. (18th June 2014) - Wiersema, J. H.
Abstract: A recent (2011) attempt to change the previously designated type of the name of a duckweed species is discussed. Lemna punctata was first applied by Meyer in 1818 to a plant collected from South America, but original specimens have not been located. A prior neotype designation associated this name with a species native to parts of Asia, Australia and the Pacific, and widely introduced elsewhere, including South America. The species is generally treated by taxonomists in the genus Spirodela (either as S. punctata or the synonym S. oligorrhiza ) or, more recently, as the sole member of the new (1999) genus Landoltia (as L. punctata ). If accepted, this 2011 attempt to re‐neotypify L. punctata would disrupt the names of two duckweed species as well as that of Landoltia . Nomenclatural arguments against accepting this new typification are provided, thereby supporting the continued usage of Landoltia in the sense intended by its original authors.